The Evolution and expression analysis of USP gene family in Solanum - Xu, Ruiqiang; Wang, Zhongyu; Chen, Zhaolong; Wang, Zepeng; Meng, Qingyuan; Li, Ning; Qin, Yong (Frontiers in Plant Science, 2025)
As natural environments degrade and extreme weather events become more frequent, humanity increasingly faces the challenge of producing crops under various complex and adverse conditions. Improving crop adaptability has become crucial. Universal stress proteins (USPs) are a class of small molecular proteins widely found in plants, capable of withstanding various biotic and abiotic environmental stresses, including temperature stress, drought, nutrient deficiency, oxidative imbalance, salt and heavy ion toxicity, and pathogenic infections. Enhancing our understanding of USPs holds significant potential for improving plant stress resilience. This study focuses on 13 species of Solanum, including cultivated and wild tomatoes, and systematically identified 438 members of the USP gene family through bioinformatics approaches. Phylogenetic analysis reveals that major USP members are conserved within Solanum, with interspecies differences in USP numbers primarily attributed to copy number variation (CNV). Through synteny and homology analyses, we found that USP27 and USP28 are unique to tomatoes, while the homologous gene of USP19 is absent in cultivated tomatoes. Notably, five unique USP genes are present in S. pennellii, which is characterized by its early differentiation and resistance advantages. Ka/Ks analysis indicates that only the USP10/21 homologous gene pair has undergone positive selection in wild tomatoes, while all other genes are subject to strong negative selection. The USPs in Solanum exhibit high consistency in domain characteristics, sequence conservation, and types of promoter regulatory elements, although there are substantial differences in the number of these elements. Utilizing publicly available data, we identified eight USPs that have undergone domestication or improvement selection, particularly noting the tissue-specific expression patterns of domesticated SolycUSP3/28/30. Through graph pangenome analysis, we screened 12 USPs covered by high-confidence structural variants, which primarily disrupt the intron regions of USPs, leading to significant differences in their expression responses to salt stress. We anticipate that these findings will provide a theoretical foundation and prior knowledge for further understanding and application of USP in plants.